Hegemoni Kekuasaan Pada Novel “Si Putih” Karya Tere Liye (Teori Gramsci) - Anisa Triana Octavia; Nazwa Rahmawati; Supriyono Supriyono (Universitas Palan, 2024)
This study aims to examine the form of hegemony of power contained in the novel